2008
DOI: 10.1051/radiopro:2008517
|View full text |Cite
|
Sign up to set email alerts
|

The effects of in utero irradiation on mutation induction and transgenerational instability in mice

Abstract: It is well known that the developing embryo is especially sensitive to ionising radiation. However, to date little is known about the long-term effects of in utero exposure on mutation rates during adulthood. To evaluate the effects of in utero irradiation on mutation induction and transgenerational instability, BALB/c pregnant mice (Theiler stage 20, 12 days of gestation) were exposed to 1 Gy of acute X-rays. The in utero exposed 8-week-old males and females were mated to control partners. To evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…No increase in the frequency of micro-satellite mutations was observed in the progeny of irradiated C. elegans, although mutations at tandem-repeat loci have been widely used as marker of RIGI in mammals and in cultured mammalian cells [8,12,17,18,[24][25][26]43,44]. This indicates that, at the genetic (DNA) level, the processes associated with RIGI in C. elegans may be quite different from those in mammalian cells.…”
Section: Discussionmentioning
confidence: 81%
“…No increase in the frequency of micro-satellite mutations was observed in the progeny of irradiated C. elegans, although mutations at tandem-repeat loci have been widely used as marker of RIGI in mammals and in cultured mammalian cells [8,12,17,18,[24][25][26]43,44]. This indicates that, at the genetic (DNA) level, the processes associated with RIGI in C. elegans may be quite different from those in mammalian cells.…”
Section: Discussionmentioning
confidence: 81%
“…The persistently increased rate of mutation in the non-exposed offspring of the irradiated parents was called transgenerational genomic instability [162]. An increase in the mutation rate of the first-and second-generation offspring of irradiated male mice was reported in many studies [163][164][165]. In particular, Barber et al [164] suggested that a genome-wide destabilization after fertilization was involved in the transgenerational RIGI.…”
Section: In Vivo Studies On Rigi Using Animal Modelsmentioning
confidence: 96%
“…The very high spontaneous mutation rate potentially makes the analysis of length change mutations occurring at ESTR loci an attractive approach for monitoring germline mutation induction in mice. Since 1993, these loci have extensively been used for the analysis of mutation induction in the germline of male mice exposed to ionizing radiation, chemical mutagens, and anticancer drugs [68][69][70][71][72][73][74], in addition to environmental air pollutants [75][76][77][78][79]. In the early studies, ESTR mutations were detected using a pedigree-based approach by profiling DNA samples extracted from all parents and their offspring.…”
Section: Expanded Simple Tandem Repeat (Estr) Assaysmentioning
confidence: 99%